An Outlook on Strategic Framework Development Needs of Roles and Involvement of Joint Property Management in High Rise Green Buildings in Malaysia - Darul Nafis Abas; Rozana Zakaria; Eeydzah Aminuddin; Redzuan Abdullah; Jam Shahzaib Khan; Shaza Rina Sahamir (Chemical Engineering Transactions, 2018)
In Malaysia, high-rise residential buildings either with green building design or conventional, is still facing challenges associated with the property management. Uncertainty measure the financial obligations allocated for managing the property are among the key challenges. The management of high rise building is a multitasking and multidiscipline function that integrates various stakeholders. Malaysia recently has introduced the new Strata Management Act 2013, with a lot of improvement for strategically enhancing the management of strata building for the benefit of all, especially the proprietor, management body, management agent and occupants. It is hypothesised that the sustainable practices and methods through integrated design and joint body to manage high rise buildings will significantly play a major role to resolve the arising issues of property management. This paper aims to highlight the ongoing research development on strategic framework of role and involvement of consulting property management during the early stage of project development phase of high rise residential green buildings. It emphasises the importance of facilities manager contributions at the development phase of high-rise residential buildings to minimise their maintainability and clashing problems faced during the phase of occupancy. This paper briefs the proposed research development that planned to employ mix methods of qualitative and quantitative survey. In this study, the preliminary literature review lead for better understanding of Joint Property Management (JPM). The future outcome of this research is very useful as a Term of Reference (TOR) to the project team in green building development process. It is important for facilities manager to get involved in the whole life cycle of high rise residential green buildings development.